NASPGHAN Clinical Report: Surveillance, Diagnosis, and Prevention of Infectious Diseases in Pediatric Patients With Inflammatory Bowel Disease Receiving Tumor Necrosis Factor-α Inhibitors. Issue 1 (July 2016) - Ardura, Monica I.; Toussi, Sima S.; Siegel, Jane D.; Lu, Ying; Bousvaros, Athos; Crandall, Wallace
Abstract : ABSTRACT: Children and adolescents with inflammatory bowel disease (IBD) receiving therapy with tumor necrosis factor α inhibitors (anti-TNFα) pose a unique challenge to health care providers in regard to the associated risk of infection. Published experience in adult populations with distinct autoinflammatory and autoimmune diseases treated with anti-TNFα therapies demonstrates an increased risk of serious infections with intracellular bacteria, mycobacteria, fungi, and some viruses; however, there is a paucity of robust pediatric data. With a rising incidence of pediatric IBD and increasing use of biologic therapies, heightened knowledge and awareness of infections in this population is important for primary care pediatricians, pediatric gastroenterologists, and infectious disease (ID) physicians. This clinical report is the result of a consensus review performed by pediatric ID and gastroenterology physicians detailing relevant published literature regarding infections in pediatric patients with IBD receiving anti-TNFα therapies. The objective of this document is to provide comprehensive information for prevention, surveillance, and diagnosis of infections based on current knowledge, until additional pediatric data are available to inform evidence-based recommendations. Abstract : Supplemental Digital Content is available in the text